Smart Module Design: Innovation in Learning Media Technology-Based Character Education - Paizah Paizah; Hatnusen Hatnusen; Fristian Hadi Putra (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The purpose of this study is to determine whether the Smart Module learning media is valid for use and how the student learning outcomes are after using this module. The success or failure of a learning process, especially in Islamic religious education that focuses on character education, is determined by the learning media used. In realizing this success, a problem arises, namely that teachers are still monotonous in using learning media so that learning cannot be received properly by students. Seeing this problem, researchers created a new innovation, the Smart Module, a technology-based character education learning media innovation, namely technology that can combine the virtual world with the real world at the same time. This study uses the R & D type with the Borg and Gall development model. Data collection techniques are carried out through observation, questionnaires, literature studies, documentation and trials, then analyzed using media expert validation analysis techniques, material expert validation analysis techniques and trial analysis techniques. The results of this study indicate that the Smart Module has a validity level of 92% and can improve student learning outcomes.